The Role And Contribution Of Women Rice Farm Workers In Household Income (Case Study Of A Family Of Rice Farmers In Waiketam Baru Village, Bula Barat District, East Seram Regency) - Fauzelia A. Mahad; Ir. Felecia P. Adam, M.Sc; Maisie T. F. Tuhumury, S.P., M. Agribus (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to find out: (i) The role of women rice farm workers in household income in Waiketam Baru Village, West Bula District, East Seram Regency; (ii) The contribution of women farm workers in household income in Waiketam Baru Village, West Bula District, East Seram Regency. This type of research uses qualitative and quantitative. Respondents in this study amounted to 31 peoples with determination techniques using Purposive Sampling techniques, namely informant determination techniques based on certain criteria, data collection techniques, namely observation, interviews and documentation. The results showed that: (i) The role of women rice farm workers is greater when carrying out public activities (44%), domestic activities (36%) and social (20%). The division of roles carried out by women (wives) makes her divide her time in taking care of the household and looking for additional income to help the increasing needs of the household. It can be seen that the role of women (wives) is very helpful in household income; (ii) The average income of women rice farm workers is Rp 1,432,258 and has a contribution to household income of 21.73%. The percentage of contribution to total household income is said to be moderate because ˂50%. While the income of men (husbands) of rice farmers averages Rp 3,247,312 and has a household contribution of 76.60%. The average contribution of the income of men (husbands) is greater than the income of women (wives). The contribution made by working women (wives) is fully in helping family income.